European Impacts on Coastal Eastern Tasmania: Insight from a High-Resolution Palynological Analysis of a Salt-Marsh Core - Moss, Patrick T.; Gehrels, W. Roland; Callard, S. Louise (Frontiers in Ecology and Evolution, 2016)
A high-resolution pollen and micro-charcoal (>5 μm) record has been produced from a short sediment (50 cm) core recovered from a salt marsh in the Little Swanport Estuary, eastern Tasmania. This record suggests that there are four phases associated with the European settlement of the region. An initial phase from around 1830 to 1858 AD, which is similar to the previous Aboriginal period; a relatively low impact transitional phase from 1859 to 1898 AD; a rapid and marked deforestation period from 1899 to 1932 AD; and establishment of the contemporary landscape, with reforestation occurring, but with marked differences in species composition (i.e. greater representation of exotic taxa and altered understorey composition) from 1933 to 2006 AD. Key similarities are seen across Australia with the European settlement phase (i.e. addition of exotic taxa, deforestation and/or changes in vegetation composition, alterations in fire regimes and increased sedimentation rates), but high-resolution analysis suggests that these impacts may manifest in different ways depending on the local environmental setting and/or historical context of the settlement location. Furthermore, Amaranthaceae pollen representation appears to be impacted by changes in sea level. However, other factors such as human modifications, particularly grazing, and climate variability may play additional roles and further research is required to disentangle the relative effects of these factors.